Recent Advances in the Catalytic Functionalization of "Electrophilic" Indoles. Issue 3 (18th February 2020) - Cerveri, Alessandro; Bandini, Marco
Abstract : When "dark" is bright : the scarcely explored electrophilic profile of the indolyl core ( dark‐side ) continues to inspire developments in organic synthesis by means of new catalytic methodologies. Recent advancements in the field enabled molecular diversity and complexity to be effectively realized within heterocyclic chemistry. Abstract : The "dark‐side" of indole reactivity (i.e. electrophilicity) is facing new horizons with the employment of metal‐based as well as organocatalytic tools.